Stimulasi Pertumbuhan Kina Belum Menghasilkan (TBM) dengan Aplikasi Konsentrasi BAP Setelah Fase Pembentukan Batang - Yudithia Maxiselly; Rafika Arum Sari; Mira Ariyanti (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
Cinchona is plantation commodity that useful as medicine material. Productivity of cinchona is influenced by growth phase on young plant. For increasing the productivy of cinchona should be applied stem shaping and combine with growth regulator. This research aims to get the precise concentration of growth regulator for young cinchona after stem shaping. The experiment was observed at Ciparanje field station of Agriculture Faculty, Padjadjaran University, Jatinangor. It used randomized block design with 6 treatments and 4 replications (3 plants for each plot). The treatments were 6 levels of BAP (0 ppm, 30ppm, 60ppm, 90 ppm, 120ppm and 150 ppm). The result showed that BAP level had significant effect for growing of young cinchona. 30 ppm of BAP influenced branch growth meanwhile 90 ppm and 150 ppm had significant effect on leaves number and stem diameter was influenced by all of BAP concentrations.